PELATIHAN UJI KOMPETENSI BAHASA ASING UNTUK MENINGKATKAN KEMAMPUAN BAHASA ASING MAHASISWA BARU - Yurianto, Ramdhan; Apriliana, Lulu Maulidia (LPPM STAIMAS WONOGIRI, 2023)
The industrial revolution 5.0 has an impact on all fronts, including the line of education, one of the proofs is that with the existence of multilingualism in education, education that was previously only bilingual is now multilingual. This is due to the ease of exchange of foreign students or international classes organized by higher education institutions. New students are very suitable prey to be introduced to the importance of foreign language competency tests, opportunities and challenges and there are training activities or language competency exam practices, so it is necessary to have special training that can support or improve the foreign language skills of new students. This commotion finally moved the administrators of student organizations at UIN Saizu Purwokerto to facilitate new students to introduce foreign language competency tests. This service focuses on providing an introduction to the importance of foreign language competency tests, their opportunities and challenges, as well as training on foreign language competency exams for new students. The method used is participatory action research (PAR) through the delivery of material and training on foreign language competency tests. The result of this service is the increase in new students' knowledge about the importance of Arabic language competency tests, the opportunities and challenges of mastering languages in the era of industry 5.0 revoulis and understanding the practice or simulation of language competency tests.